V Premio de pintura 20/12 : BANCOR (Córdoba : Banco de Córdoba, 2012)
Jurado Daniel Capardi Pablo González Padilla María Dolores Moyano Raúl Santana
Museo Superior de Bellas Artes. Evita- Palacio Ferreyra- Córdoba
Keywords: Catálogos de arte; Pintura; BANCOR; Pablo Scheibengraf; Martínez Archina, Ariel; Perrotta, Claudia; Manuel Coll; Noelia Farías